Ozone loss and chlorine activation in the Arctic winters 1991?2003 derived with the TRAC method - Tilmes, S.; Müller, R.; Grooss, J.-U.; Russell Iii, J. M. (CCSD, 2004)
International audience In this paper chemical ozone loss in the Arctic stratosphere was investigated for twelve years between 1991 and 2003. The accumulated local ozone loss and the column ozone loss were consistently derived mainly on the basis of HALOE observations. The ozone-tracer correlation (TRAC) method is used, where the relation between ozone and a long-lived tracer is considered over the lifetime of the polar vortex. A detailed quantification of uncertainties was performed. This study demonstrates the interaction between meteorology and ozone loss. The correlation between temperature conditions and chlorine activation becomes obvious in the HALOE HCl measurements, as well as the dependence between chlorine activation and ozone loss. Additionally, the degree of homogeneity of ozone loss is shown to depend on the meteorological conditions, as there is a possible influence of horizontal mixing of the air inside a weak polar vortex edge. Results estimated here are in agreement with the results obtained from other methods. However, there is no sign of very strong ozone losses as deduced from SAOZ for January considering HALOE measurements. In general, strong accumulated ozone loss is found to occur in conjunction with a strong cold vortex containing a large potential area of PSCs, whereas moderate ozone loss is found if the vortex is less strong and moderately warm. Hardly any ozone loss was calculated for very warm winters with small amounts of the area of possible PSC existence (A PSC ) during the entire winter. Nevertheless, the analysis of the relationship between A PSC (derived using the PSC threshold temperature) and the accumulated ozone loss indicates that this relationship is not a strictly linear relation. An influence of other factors could be identified. A significant increase of ozone loss (of ?40 DU) was found due to the different duration of illumination of the polar vortex in different years. Further, the increased burden of aerosols in the atmosphere after the Pinatubo volcanic eruption ...